Oxidative Coupling Assay for Mesalazine Determination in Pharmaceuticals and Spiked Human Plasma Utilizing Syringic Acid - Suzan S. Taha; Diyar S. Ali (Journal of Spectroscopy)
This study reports on developing a simple, cost-effective, highly sensitive spectrophotometric method for measuring mesalazine (MSZ). The method utilizes the oxidative coupling of MSZ with syringic acid (4-hydroxy 3,5-dimethoxybenzoic acid) in the presence of dissolved oxygen under alkaline conditions to form a stable indophenol dye with a characteristic blue color, which can be measured at 615 nm. Beer’s law was found to be obeyed over the range of 1.25–50 µg·mL−1, with a molar absorptivity of 0.53 × 104 mol−1·L−1·cm−1. Moreover, the method exhibited excellent sensitivity, with a limit of detection (LOD) of 0.093 µg·mL−1 and a limit of quantitation (LOQ) of 0.282 µg·mL−1. The proposed method was found to be selective, as it could effectively detect MSZ in the presence of certain interfering species. The proposed method was validated according to current ICH guidelines and demonstrated good accuracy, with recoveries ranging between 98 and 100% and a relative standard deviation of less than 0.6%. Overall, this method provides a promising tool for the sensitive and accurate determination of MSZ in its pure form, pharmaceutical formulations, and biological samples.